Evaluation and Management of Mid-shaft Clavicle Fractures in Adolescents: Current Concepts Review - Jasty, Naveen; Study Group, FACTS; Heyworth, Benton (Journal of the Pediatric Orthopaedic Society of North America, 2020)
The rate of operative fixation for completely displaced mid-shaft clavicle fractures in adolescents has been increasing yearly over the last decade, largely driven by studies of adult populations, in whom the rate of nonunion is approximately 15% with non-operative treatment. However, nonunion and symptomatic malunion in younger populations remain rare. Recent studies suggest that functional outcomes are similar between conservative management and operative fixation in adolescents, with higher rates of complications and slightly decreased time to return to sport with operative fixation. Implant-related symptoms after surgery remains an important consideration, due to potential for reoperation for implant removal. Additionally, the cost of operative fixation is significantly higher than that of non-operative management. The aim of this review is to summarize the salient historical and more recent literature regarding displaced mid-shaft clavicle fractures in order to better understand treatment considerations and the natural history of these fractures in the adolescent.